Berries and Small Fruits: Safe Handling Practices for Consumers - Amy Simonne (EDIS)
Small fruits and berries include table grapes, strawberries, blueberries, blackberries, raspberries, and kiwi fruit. These fruits are very tender and delicate. Most of these fruits are often packaged in the field without washing. Since the fruits are grown in a natural environment, they may be contaminated with harmful bacteria. Here are steps that you can take to reduce your risk of foodborne illness from these delicious fruit. This publication is FCS8741, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. Publication date: November 2002.